2017
DOI: 10.1136/bmj.j356
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes in patients undergoing arthroscopic partial meniscectomy for traumatic or degenerative meniscal tears: comparative prospective cohort study

Abstract: Objectives To compare patient reported outcomes from before surgery to 52 weeks after surgery between individuals undergoing arthroscopic partial meniscectomy for traumatic meniscal tears and those for degenerative meniscal tears. Design Comparative prospective cohort study. Setting Four public orthopaedic departments in the Region of Southern Denmark. Participants were recruited between 1 February 2013 and 31 January 2014, and at one of the original four hospitals from 1 February 2014 to 31 January 2015. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 46 publications
5
57
1
Order By: Relevance
“…More than 60% of all SMT cases in our cohort reported having no mechanical symptoms as reported on individual questions from the KOOS questionnaire. This result is comparable with other cohorts with meniscal tears [3,5,21,22,51]. Also, mechanical symptoms, when present, do not arise exclusively from meniscal tears and may be positive in other disorders such as ACL tear or osteoarthritis [3,6].…”
Section: Discussionsupporting
confidence: 84%
“…More than 60% of all SMT cases in our cohort reported having no mechanical symptoms as reported on individual questions from the KOOS questionnaire. This result is comparable with other cohorts with meniscal tears [3,5,21,22,51]. Also, mechanical symptoms, when present, do not arise exclusively from meniscal tears and may be positive in other disorders such as ACL tear or osteoarthritis [3,6].…”
Section: Discussionsupporting
confidence: 84%
“…The findings of Salata et al  are in concordance with Englund et al 56 who found that degenerative meniscal tears result in worse clinical and radiological outcome after 16 years in 155 patients undergoing APM. By contrast, a recently published and methodologically robust study of Thorlund et al 57 reported no clinically relevant difference in patient-reported knee function and satisfaction between degenerative and traumatic meniscal tears after 12 months. This is in line with the results of the current systematic review, in which no difference in patient-reported clinical outcome between non-traumatic and traumatic tears was found as well.…”
Section: Discussionmentioning
confidence: 85%
“…Different approaches to classify meniscal tears as traumatic or degenerative can be found in the literature. Some are based on symptom onset alone,69 whereas others use a combination of age and symptom onset70 as osteoarthritic changes and meniscal degeneration are linked to older age. Clearly, a ‘gray zone’ exists where it can be difficult to discern.…”
Section: Discussionmentioning
confidence: 99%